Indian Dairy Sector-Status and Policy Options - Gupta, Meenakshi; Sharma, Vikas (Indian Journal of Marketing, 2009)
Agricultural development has been associated mainly with an increase in the production of cereals. In India majority of the people have less than one hectare of land. Due to small holdings these cultivators are unable to meet the basic requirements for their livelihood. While on the other hand, growing urbanization and income levels resulted in an increased purchasing power, higher literacy there by health and nutrition concerns and changes in life style might have provided an impetus to an increased demand for this sector. Scarcities of resources in terms of livestock lead to the need for major Policy reforms in the dairy sector. India dairy sector during past 6 decades had shown consistent growth trends which in turn resulted in its best ranking in world dairy scenario, which is only possible with balanced growth of livestock and proper dairy infrastructure development throughout the country.